2021
DOI: 10.1007/s00402-021-04070-0
|View full text |Cite
|
Sign up to set email alerts
|

How does sleep apnea impact outcomes following primary total hip arthroplasty for femoral neck fractures: a matched-control analysis

Abstract: Background Cross-sectional studies have demonstrated that the prevalence of sleep apnea (SA) to be increasing within the United States. While studies have shown the association of SA and its association on complications following elective orthopedic procedures, well-powered studies investigating its impact in a traumatic setting are limited. The purpose of this study was to determine whether SA patients undergoing primary total hip arthroplasty (THA) for femoral neck fractures have higher rates of: (1) hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Both obstructive sleep apnea (OSA) and obesity have been found to result in hypercarbia [ 16 , 17 ]. OSA has been shown to increase the length of hospital stay, medical complications including surgical site infections, and healthcare costs for patients with total hip replacements after femoral neck fracture [ 18 ]. Multiple studies have demonstrated that obesity increases the risk of PJI in TJR [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both obstructive sleep apnea (OSA) and obesity have been found to result in hypercarbia [ 16 , 17 ]. OSA has been shown to increase the length of hospital stay, medical complications including surgical site infections, and healthcare costs for patients with total hip replacements after femoral neck fracture [ 18 ]. Multiple studies have demonstrated that obesity increases the risk of PJI in TJR [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%